Hierarchical Co9S8 hollow microspheres as multifunctional electrocatalysts for oxygen reduction, oxygen evolution and hydrogen evolution reactions - Zhang, Yatian; Chao, Shujun; Wang, Xiaobing; Han, Huijuan; Bai, Zhengyu; Yang, Lin (Electrochimica acta, 2017)
Making efficient trifunctional non-precious metal catalysts for simultaneously catalyzing oxygen reduction reaction (ORR), oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in same electrolyte is very important to bring energy conversion and storage systems into realities. Herein, hierarchical Co9S8 hollow microspheres had been designed and synthesized by a facile hydrothermal reaction at 140°C (denoted as Co9S8 HMs-140). The properties and formation process of the Co9S8 HMs-140 were systematically investigated. Owing to the composition and structure features, the Co9S8 HMs-140 can be used as a trifunctional catalyst for ORR, OER and HER in the same alkaline electrolyte. The Co9S8 HMs-140 shows reasonable ORR and HER performance. Additionally, OER performance of the Co9S8 HMs-140 is superior to that of RuO2, such as a low onset potential (1.47V vs. RHE) and high stability. Furthermore, due to the bifunctional OER and HER activity of the Co9S8 HMs-140, the Co9S8 HMs-140 affords an O2 efficiency of 31 mmolh−1 and a H2 efficiency of 62mmolh−1 at 1.60V in 1M KOH solution under the given time range, exhibiting a 96% faradaic yield in the process of full water splitting to produce O2 and H2. The present work will provide a promising prospect for the development of multifunctional transition metal sulfides as effective electrocatalysts for sustainable energy systems.